2021
DOI: 10.1021/acsaelm.0c00997
|View full text |Cite
|
Sign up to set email alerts
|

Strain Relaxation via Phase Transformation in High-Mobility SrSnO3 Films

Abstract: SrSnO3 (SSO) is an emerging ultrawide band gap (UWBG) semiconductor with potential in high-power applications. In-plane compressive strain was recently shown to stabilize the high-temperature tetragonal phase of SSO at room temperature (RT), which exists at T ≥ 1062 K in bulk. Here, we report on the study of strain relaxation in the epitaxial, tetragonal phase of Nd-doped SSO films grown on GdScO3 (110) (GSO) substrates and how it influences the electronic transport properties. The thinnest SSO film (thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
1
14
1
Order By: Relevance
“…Since the bulk lattice parameters of the Pnma phase are 4.035 and 4.033 Å along the a – and c + directions, respectively, the initial growth of a – a – c + alignment with larger lattice parameters being the in-plane axes can be stabilized with the imposed tensile strain. It should be noted that while recent studies have reported strain-driven phase transition of SrSnO 3 to the tetragonal I 4/ mcm phase with an octahedral rotation pattern of a 0 a 0 c – , , XRD result from the films studied here shows significantly smaller (∼3%) out-of-plane lattice parameters compared to those of the tetragonal phase and, therefore, excludes the possibility of tetragonal phase formation.…”
Section: Resultscontrasting
confidence: 47%
See 2 more Smart Citations
“…Since the bulk lattice parameters of the Pnma phase are 4.035 and 4.033 Å along the a – and c + directions, respectively, the initial growth of a – a – c + alignment with larger lattice parameters being the in-plane axes can be stabilized with the imposed tensile strain. It should be noted that while recent studies have reported strain-driven phase transition of SrSnO 3 to the tetragonal I 4/ mcm phase with an octahedral rotation pattern of a 0 a 0 c – , , XRD result from the films studied here shows significantly smaller (∼3%) out-of-plane lattice parameters compared to those of the tetragonal phase and, therefore, excludes the possibility of tetragonal phase formation.…”
Section: Resultscontrasting
confidence: 47%
“…This is in contrast to the previously reported situation, where the compressive strain on GdScO 3 (110) substrates is relaxed as the SLSO film becomes thicker. 44 , 45 Figure 4 c illustrates the rocking curves for 105 nm 4% SLSO, 33 nm SrHfO 3 , 55 nm BaHfO 3 and the MgO (001) substrate. The MgO (001) single-crystal substrate has a sharp peak shape with full width at half-maximum (FWHM) of around 0.032.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The room-temperature Hall-effect measurements yielded a carrier concentration of 1.9 × 10 19 cm –3 in this sample. Figure (a) shows an insulating-like behavior, i.e., an increasing sheet resistance with decreasing temperature, which we attribute to the disorder at the surface . A sharp rise in R s was observed at T < 6 K. To investigate the low-temperature transport mechanism, we performed Zabrodski analysis (see inset of Figure (a)), yielding a slope of 0.6.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2(a) shows an insulating-like behavior, i.e., an increasing sheet resistance with decreasing temperature, which we attribute to the disorder at the surface. 32 A sharp rise in R s was observed at T < 6 K. To investigate the low-temperature transport mechanism, we performed Zabrodski analysis (see inset of Figure 2(a)), yielding a slope of 0.6. This result reveals that the low-temperature (T < 6 K) insulating behavior is associated with the Efros−Shklovskii (ES) variable range hopping.…”
Section: ■ Introductionmentioning
confidence: 99%